Pengembangan Media Pembelajaran Playing Cards dan Handout Dalam Model Pembelajaran Make A Match Untuk Melatih Keaktifan Siswa - Fauriza Choirun Nisa; Mustika Wati; Sri Hartini (Universitas Lambung Mangkurat, 2015)
Low activity of students during the learning is caused by lack of instructional media. It is necessary to develop an insctructional media which is fun to make students active and motivated. The purpose of this research is to produce playing cards and handout which are proper for learning model type make a match to train students activity during the learning. This study is a research and development that used ADDIE (analysis, design, develop, implement, evaluate) as a development model. The subject of this research is students at seventh grade of SMPN 24 Banjarmasin. The instrument of collecting data are the sheet of validity media, activity assessment instrument, and questionnaire responses. The result of this research shows that (1) the playing cards developed is valid used as instructional media for learning model type make a match by a little revision, (2) handout which is developed is valid used as instructional media by a little revision, (3) the average of students activity in every meeting include visual, verbal, motor and emotional aspect give activity level of very active, (4) students give excellent response to the quality aspects of media, the influences of media and studying acting and also a good respons to the material.